Godzilla and the Japanese after World War II: From a scapegoat of the Americans to a saviour of the Japanese - Ikeda, Yoshiko (Acta Orientalia Vilnensia, 2011)
[full article and abstract in English] This paper examines how five Godzilla films illuminate the complicated relationship between Japan and the United States over the use of nuclear weapons. The United States dropped the first atomic bombs on Japan and created the first nuclear monster film, The Beast from 20,000 Fathoms (1953), which inspired the Godzilla series. The popularity of these Godzilla films derives from skilfully grappling with the political, social and cultural problems created by the use of nuclear weapons and science/technology, both inside Japan and in relations between Japan and the United States. This paper takes a historical perspective and shows how the Godzilla characters reflect these attitudes across time, moving from a scapegoat for the Americans to a saviour of the Japanese.